Tinjauan Filsafat Sains pada Konsep Horsepower dalam Pembelajaran Fisika - Dens Asbanu (Pendidikan Fisika Universitas Nurul Huda, 2024)
Teaching physics concepts using a philosophy of science approach is important for understanding how physical scientists develop theories. The concepts of quantities, units, and dimensions in physics, such as horsepower (hp), are fundamental to learning from school to college. However, there is still a lack of philosophical understanding of the concept of horsepower in the context of physics teaching, leading to a deficiency in this understanding. This study proposes a philosophical exploration of the concept of horsepower from the perspectives of epistemology, ontology, and axiology. The research methods used include in-depth literature studies, conceptual analysis, and case studies related to the implications of horsepower in automotive industrial engineering. The results demonstrate that the concept of horsepower can be examined from various philosophical perspectives, including aspects of epistemology in its development, ontology in understanding its existence, and axiology in considering the values associated with its use. This philosophical exploration not only enhances the understanding of physics concepts but also encourages deeper reflection on the relationship between humans, technology, and nature